Indirect Factors Affecting Personal Solvency: Empirical Analysis Of Lithuanian Consumer Credit Market - Daiva Jureviciene; Kamile Taujanskaite; Vytaute Sukacevskyte (European Scientific Journal, ESJ, 2016)
The aim of this article is to analyze the interrelationship between solvencies of consumer credits customers and indirect factors such as borrowing motivation as well as demographical and socioeconomic factors characterizing the borrowers’ personality. The results of this research were obtained using statistical software SPSS. Systemic scientific literature analysis, correlation analysis of randomly selected records from consumer credit contracts, Student t-test criteria application for testing hypothesis, analysis of Levine's and Pearson’s correlation criteria are used in the article. In addition, previously carried out expert evaluation research results were compared with actual consumer credit contracts data. The novelty of this research is classification of factors influencing personal solvency into direct and indirect. The influence of indirect factors (demographic, socioeconomic and borrowing motives) has been investigated in risky consumer credit market of Lithuania. The results show that the most influencing indirect factor is the purpose of consumer credit.